A New Synthesis of Gefitinib - Maskrey, Taber S.; Kristufek, Tyler; LaPorte, Matthew G.; Nyalapatla, Prasanth R.; Wipf, Peter (Synlett, 2019)
A four-step synthesis of the FDA-approved anticancer agent gefitinib was developed starting from 2,4-dichloro-6,7-dimethoxyquinazoline. Reaction temperatures were highly practical (0–55 °C), and chromatographic purifications were avoided. The ionic liquid trimethylammonium heptachlorodialuminate was used to monodemethylate the dimethoxyquinazoline core. In the final step, a selective dehalogenation was employed to provide gefitinib in 14% overall yield on a gram scale.
Keywords: ionic liquids; demethylation; nucleophilic aromatic substitution; dehalogenation; gefitinib; medicinal chemistry